Covid-19-associated pulmonary aspergillosis in mechanically ventilated patients: incidence and outcome in a French multicenter observational cohort (APICOVID) - Luc Desmedt; Matthieu Raymond; Aurélie Le Thuaut; Pierre Asfar; Cédric Darreau; Florian Reizine; Gwenhaël Colin; Johann Auchabie; Julien Lorber; Béatrice La Combe; Pierre Kergoat; Baptiste Hourmant; et al. (Annals of Intensive Care, 2024)
Abstract Background Recent studies identified coronavirus disease 2019 (COVID-19) as a risk factor for invasive pulmonary aspergillosis (IPA) but produced conflicting data on IPA incidence and impact on patient outcomes. We aimed to determine the incidence and outcomes of COVID-19-associated pulmonary aspergillosis (CAPA) in mechanically ventilated patients. Methods We performed a multicenter retrospective observational cohort study in consecutive adults admitted to 15 French intensive care units (ICUs) in 2020 for COVID-19 requiring mechanical ventilation. CAPA was diagnosed and graded according to 2020 ECMM/ISHAM consensus criteria. The primary objective was to determine the incidence of proven/probable CAPA, and the secondary objectives were to identify risk factors for proven/probable CAPA and to assess associations between proven/probable CAPA and patient outcomes. Results The 708 included patients (522 [73.7%] men) had a mean age of 65.2 ± 10.8 years, a median mechanical ventilation duration of 15.0 [8.0–27.0] days, and a day-90 mortality rate of 28.5%. Underlying immunosuppression was present in 113 (16.0%) patients. Corticosteroids were used in 348 (63.1%) patients. Criteria for probable CAPA were met by 18 (2.5%) patients; no patient had histologically proven CAPA. Older age was the only factor significantly associated with probable CAPA (hazard ratio [HR], 1.04; 95% CI 1.00–1.09; P = 0.04). Probable CAPA was associated with significantly higher day-90 mortality (HR, 2.07; 95% CI 1.32–3.25; P = 0.001) but not with longer mechanical ventilation or ICU length of stay. Conclusion Probable CAPA is a rare but serious complication of severe COVID-19 requiring mechanical ventilation and is associated with higher day-90 mortality. Graphical Abstract